OPTIMIZING SPIRITUAL INTELLIGENCE ENHANCEMENT: A COMPREHENSIVE ANALYSIS OF ASMAUL HUSNA ACTIVITIES AT SMA NEGERI 3 SALATIGA - Nababan, Kristina Roseven; Mediatati, Nani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2023)
This study aims to analyze the optimization of students' spiritual intelligence through Asmaul Husna activities at SMK Negeri 3 Salatiga, which is aligned with the school's vision in producing graduates with noble character and environmental insight to compete in the global era. The research method used is a qualitative approach by exploring data through interviews, observations, and literature studies as primary data, and strengthening the results with the use of questionnaires as secondary data. The results showed that routine efforts in carrying out Asmaul Husna activities have not made a significant impact on the development of students' spiritual intelligence. Observations show that most students can merely cognitively grasp the concepts or at the knowledge level, but are not fully able to implement them in their daily lives, especially with regard to changing attitudes. Therefore, comprehensive support from all the stakeholders of the school is needed in designing a more effective strategy for developing students' spiritual intelligence. Asmaul Husna activities that are carried out every day need to be carefully monitored by the school and family, considering that the success of this activity can be assessed from significant changes in students' attitudes and behaviour, which are the initial capital in their future career development.